2007
DOI: 10.2754/avb200776030363
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Flavonoid Pomiferin on Heart Ischemia-Reperfusion

Abstract: Nečas J., L. Bartošíková, T. Florian, J. Klusáková, V. Suchý, E. Janoštíková, T. Bartošík, EM. B. El Naggar: Protective Effects of Flavonoid Pomiferin on Heart IschemiaReperfusion. Acta Vet. Brno 2007, 76: 363-370.The objective of the present 15-day study was to evaluate the cardioprotective potential of fl avonoid pomiferin isolated from the infructences of Maclura pomifera, Moraceae, against ischemia-reperfusion induced injury in rat hearts as a model of antioxidant-based composite therapy. Studies were perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…The protective capacity of quercetin against I/R injury is not limited to the myocardium but is also found in several other tissues, such as the kidney, 49,50 liver 51 and brain 52 . Considering the potential of the flavonoids as a whole, our result further supports previous studies reporting the limiting effect of flavonoids on infarct size 53–55 …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The protective capacity of quercetin against I/R injury is not limited to the myocardium but is also found in several other tissues, such as the kidney, 49,50 liver 51 and brain 52 . Considering the potential of the flavonoids as a whole, our result further supports previous studies reporting the limiting effect of flavonoids on infarct size 53–55 …”
Section: Discussionsupporting
confidence: 89%
“…Quercetin and rutin treatment significantly reduced the serum and tissue MDA levels in both normal and diabetic I/R injury. Although quercetin does not reverse oxidative stress in other organs collected from diabetic rats, 56 numerous earlier studies reveal that quercetin attenuates oxidative stress in experimental settings of I/R 51,53 . Furthermore, quercetin has a well‐proven antioxidant effect, in vitro as well as in vivo.…”
Section: Discussionmentioning
confidence: 98%
“…Although luteolinidin protects the heart through its potent inhibition of CD38, it could also exert other beneficial effects. It has been suggested that flavonoids can be protective due to their antioxidant activity (Necas et al, 2006;Chang et al, 2007). In our experiments, the dose dependence of the protection (from 5 to 50 mM) argues for relatively high potency and low toxicity for luteolinidin.…”
Section: Discussionmentioning
confidence: 63%
“…6 Furthermore, significant antioxidant activity seems to attenuate myocardial dysfunction provoked by reperfusion ischaemia. 7 In specified clinical circumstances natural synergy, as is the case in urginea maritima, containing flavonoids and scillaglycoside with its inotropic, antiarrhythmic and vaso-active action, not to say neurohumoral modulation, 8 need not be deleterious at all. With a sense of understatement one could then argue for a full circle with herbal medicine in antiquity.…”
Section: Discussionmentioning
confidence: 99%